Univariate and Simplex Optimization for The Analysis of Diphenhydramine-HCl Through Ion-pair Formation - Mohammed, A. K.; Dikran, S. B.; Alubydi, M. Abdul Sattar (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
A Simple, rapid and sensitive extractive and spectrophotometric method has been described for the analysis of diphenhyldramine â€“HCl (DPH) in pure form and in pharmaceutical formulations. The method is based on the formation of chloroform soluble ion-pair  complex with Bromophenol blue(BPB) in a phthalate buffer at pH 3.0.The extracted complex shows maximum absorbance at 410 nm. Beer's law is obeyed in the concentration range 0.2-25.0 Âµg.ml-1. The molar absorptivity and Sandell's sensitivity for the system being  2.416x104 L.mol-1.cm-1 and 0.012Âµg.cm-2, respectively. The limit of detection was found to be 0.155 Âµg.ml-1.           The proposed method was successfully applied to the determination of the drug in pharmaceutical formulation and satisfactory results were obtained.